AVALIAÇÃO DA COMBUSTÃO DE BIODIESEL EM MOTOR DE CICLO DIESEL - MENDES, Luís Rodrigo Benitez; SILVA, Carmem Cícera Maria da; CARVALHO, Núbia Luiza Corrêa; CESCA, Rafaela da Silva (ANAIS DO ENIC, 2017)
-